EVALUATING THE THERMAL METAMORPHISM OF CM CHONDRITES BY USING THE PYROLYTIC BEHAVIOR OF CARBONACEOUS MACROMOLECULAR MATTER - Kitajima F.; Nakamura T.; Takaoka N.; Murae T. (My University, 2002)
The degrees of thermal metamorphism of 10 CM chondrites and of the Allende CV3 chondrite were evaluated from the viewpoint of ''graphitization'' of the carbonaceous macromolecular matter by means of flash pyrolysis-gas chromatography (GC). The unheated chondrites, Yamato- (Y-) 791198, Murray and Cold Bokkeveld, yielded larger amounts and wider varieties of pyrolyzates than the chondrites strongly heated in the parent asteroids, Y-82054, Y-86695, and Belgica- (B-) 7904, and Asuka- (A-) 881334 (more strongly heated than Y-793321, which has been weakly heated, but lesser than the other strongly heated meteorites). The weakly heated chondrites, Y-793321 and A-881458, showed intermediate features. The data indicate that graphitization of the carbonaceous matter is most extreme in the strongly heated chondrites and that during graphitization, the matter has lost its labile portion, which can generate pyrolyzates such as naphthalene. In order to establish a new method for the evaluation of the degree of graphitization of chondritic carbonaceous matter, a diagram was developed to show the relationship between the total amounts of pyrolyzates with retention times later than 5 min (=SRT>5) and the ratio of the amount of naphthalene, a pyrolysis product, to SRT>5 (=SN/SRT>5). The diagram indicates a possible evolutionary pathway of graphitization of the carbonaceous matter in carbonaceous chondrites.